Blast management - Shouraki, Mohammad Kargar; Naserkheil, Ali Asghar (Видавництво Львівської політехніки, 2011)
Blast Management (BM) is composed of the combination of human resources management (HRM) principles and concepts and various methods of quality management (QM) with a financial approach. BM is made up of three aspects: hard, soft and concept and BLAST means an explosive shift in organization's mindset and thought and rapid action against it. The first aspect, hard, includes a set of managerial toots and philosophies to improve the quality and productivity with a financial approach.
Keywords: BSC (Balanced Scorecard); Lean Manufacturing; ABC/M (Activity-Based Costing/ Management); Six Sigma and TQM (Total Quality Management); HRM (Human Resource Management)